Immune-Related RNA-Binding Protein-Based Signature With Predictive and Prognostic Implications in Patients With Lung Adenocarcinoma - Xu, Lei; Li, Wanru; Yang, Ting; Hu, Siqi; Zou, Qiong; Jiao, Ju; Jiang, Ningyi; Zhang, Yong (Frontiers in Molecular Biosciences, 2022)
Background: Dysregulation of RNA-binding proteins (RBPs) in cancers is associated with immune and cancer development. Here, we aimed to profile immune-related RBPs in lung adenocarcinoma (LUAD) and construct an immune-related RBP signature (IRBPS) to predict the survival and response to immunotherapy. Methods: A correlation analysis was performed to establish a co-expression network of RBPs and immune-related genes (IRGs) to characterize immune-related RBPs in the TCGA–LUAD cohort (n = 497 cases). Then, a combination of the Random survival forest (RSF) and Cox regression analysis was performed to screen the RBPs and establish IRBPS. This was followed by independent validation of IRBPS in GSE72094 (n = 398 cases), GSE31210, (n = 226 cases), and GSE26939 (n = 114 cases). Differences between the low- and high-risk groups were compared in terms of gene mutations, tumor mutation burden, tumor-infiltrating lymphocytes, and biomarkers responsive to immunotherapy. Results: DDX56, CTSL, ZC3H12D, and PSMC5 were selected and used to construct IRBPS. The high-risk scores of patients had a significantly worse prognosis in both training and testing cohorts (p < 0.0001 and p < 0.05, respectively), and they tended to be older and have an advanced TNM stage. Furthermore, IRBPS was a prognostic factor independent of age, gender, smoking history, TNM stage, and EGFR mutation status (p = 0.002). In addition, high-risk scores of IRBPS were significantly correlated with tumor-infiltrating lymphocytes (p < 0.05). They also had a high level of PD-L1 protein expression (p < 0.01), number of neoantigens (p < 0.001), and TMB (p < 0.001), implying the possible prediction of IRBPS in the immunotherapy of LUAD. Conclusion: The currently established IRBPS encompassing immune-related RBPs might serve as a promising tool to predict survival, reflect the immune microenvironment, and predict the efficacy of immunotherapy among LUAD patients.